1991
DOI: 10.1111/j.1365-2125.1991.tb03903.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct and metabolism‐dependent toxicity of sulphasalazine and its principal metabolites towards human erythrocytes and leucocytes.

Abstract: 6.8 ± 0.3%), the retention time of which on h.p.l.c. corresponded to synthetic sulphapyridine hydroxylamine. The half-life of sulphapyridine hydroxylamine in phosphate buffer (pH 7.4) was found to be 8.1 min. 5 In the absence of microsomes and NADPH, sulphapyridine hydroxylamine caused a concentration-dependent (10-500 FM) increase in methaemoglobinaemia (2.9%-24.4%) and cytotoxicity (5.4%-51.4%), whereas sulphasalazine, sulphapyridine, 5-hydroxy sulphapyridine and 5-aminosalicylic acid had no effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Neutrophil and lymphocyte membrane integrity was assessed by trypan blue dye exclusion as described previously ( Pirmohamed et al ., 1991 ). Cells were incubated with SMX, SMX‐NHOH or SMX‐NO (1–1000 μ M ) in Dulbecco's PBS (1 ml, pH 7.4) in a shaking water bath at 37°C for 1 h. Data represents the percentage of trypan blue stained cells/total number of cells.…”
Section: Methodsmentioning
confidence: 99%
“…Neutrophil and lymphocyte membrane integrity was assessed by trypan blue dye exclusion as described previously ( Pirmohamed et al ., 1991 ). Cells were incubated with SMX, SMX‐NHOH or SMX‐NO (1–1000 μ M ) in Dulbecco's PBS (1 ml, pH 7.4) in a shaking water bath at 37°C for 1 h. Data represents the percentage of trypan blue stained cells/total number of cells.…”
Section: Methodsmentioning
confidence: 99%
“…However, when normal subjects were supplemented with ascorbate, leukocyte ascorbate levels increased, and both direct and delayed cytotoxicity decreased significantly. Others have shown that exogenous ascorbate decreases sulfonamide cytotoxicity in vitro (Pirmohamed et al, 1991). Our results suggest that pharmacologically achievable concentrations of ascorbate are likely to decrease the cytotoxicity of even high concentrations of SMX-NO in vivo.…”
Section: Discussionmentioning
confidence: 46%
“…Nitric oxide (14), bacterial toxins (15) and many drugs (16) can induce methemoglobin formation. Normally the haemoglobin molecule and the membrane of the erythrocyte are protected by the reducing systems within the erythrocyte.…”
Section: Discussionmentioning
confidence: 99%